Analisis Medan Magnet Di Luar Sumbu Solenoida Dengan Sensor Efek Hall SS49E 3 Dimensi - Saparullah Saparullah; Hana Indah Pertiwi Arimi; Resti Ayu Ningrum (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2025)
This study analyzes the distribution of the magnetic field outside a solenoid using an experimental and theoretical approach with the Hall effect sensor SS49E, amplified by the IC LM358. Measurements were conducted in three dimensions to characterize the magnetic field along the solenoid. The experimental results indicate that the magnetic field distribution is non-uniform, with the highest intensity near the solenoid's ends and a minimum value at its center. Empirical data were compared with a theoretical model based on Biot-Savart’s law, showing a 98% correlation, which indicates the accuracy of the measurement method used. This research provides additional insights into the magnetic field outside solenoids and it can be an excellent school project for undergraduate students.